2017
DOI: 10.1177/2048872617708974
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of early treatment response by rapid cardiothoracic ultrasound in acute heart failure: Cardiac filling pressures, pulmonary congestion and mortality

Abstract: E/e' seemed like the most useful congestion parameter for monitoring early treatment response, predicting prognostically beneficial resolution of pulmonary congestion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 31 publications
0
26
0
2
Order By: Relevance
“…In a single-centre study of 60 patients, the significant decrease in E/e ′ was observed as early as within the first 12 h of treatment with further decline during 48 h, contrary to the delayed response of inferior vena cava (IVC) and BNP values. 106 Change in pulmonary capillary occluded pressure was strongly correlated with change in E/e ′ at 48 h but not with BNP in 50 patients admitted to intensive care, 94 although many factors other than left atrial pressure can affect BNP levels. Non-invasive indices should be used cautiously in patients with heart failure with preserved ejection fraction because of the high variability of individual linear regression slopes relating E/e ′ and E/Vp with invasive measures.…”
Section: Echocardiography For Monitoring Filling Pressuresmentioning
confidence: 96%
See 1 more Smart Citation
“…In a single-centre study of 60 patients, the significant decrease in E/e ′ was observed as early as within the first 12 h of treatment with further decline during 48 h, contrary to the delayed response of inferior vena cava (IVC) and BNP values. 106 Change in pulmonary capillary occluded pressure was strongly correlated with change in E/e ′ at 48 h but not with BNP in 50 patients admitted to intensive care, 94 although many factors other than left atrial pressure can affect BNP levels. Non-invasive indices should be used cautiously in patients with heart failure with preserved ejection fraction because of the high variability of individual linear regression slopes relating E/e ′ and E/Vp with invasive measures.…”
Section: Echocardiography For Monitoring Filling Pressuresmentioning
confidence: 96%
“…B‐lines appear to be dynamic in nature, as they decrease in proportion to the amount of fluid removed in patients undergoing dialysis . They have also been shown to decrease with treatment of AHF . According to a recent systematic review, B‐line number changed within as few as 3 h of heart failure treatment .…”
Section: Imagingmentioning
confidence: 99%
“…Besides, in ADHF patients, IVC diameter at admission has shown prognosis utility for readmission, renal impairment, and mortality . IVC diameter has been correlated with the clinical evolution of ADHF, showing improvement in diameter and collapsibility after diuretic treatment . Finally, other studies have demonstrated the prognosis power of IVC ultrasonography, prior to discharge after hospitalization for ADHF, to predict readmission …”
Section: Introductionmentioning
confidence: 97%
“…Ohman et al measured B‐lines, natriuretic peptides, and dyspnea serially after pulmonary decongestion therapy with diuretics. Patients showing an early reduction of E/eʹ also showed a more marked reduction in B‐lines, which was the strongest prognostic predictor, again suggesting that LUS may provide a suitable marker to study the pulmonary congestion and also the therapy‐induced pulmonary decongestion phase . The proposed model of lung water cascade needs now further evidence support through prospective studies looking more systematically to the sequence of events both in pulmonary congestion and pulmonary decongestion phase.…”
Section: From Sound To Ultrasound In Imaging Lung Water In Heart Failurementioning
confidence: 96%
“…ured B-lines, natriuretic peptides, and dyspnea serially after pulmonary decongestion therapy with diuretics. Patients showing an early reduction of E/eʹ also showed a more marked reduction in B-lines, which was the strongest prognostic predictor, again suggesting that LUS may provide a suitable marker to study the pulmonary congestion and also the therapy-induced pulmonary decongestion phase 38. The proposed model of lung water cascade needs now further evidence support through prospective studies looking more systematically to the sequence of events both in pulmonary congestion and pulmonary decongestion phase.The stage is set for outcome studies comparing standard vs B-line-driven therapy in heart failure in various populations, including heart failure with reduced or preserved ejection fraction; patients with rest or only exercise-induced B-lines; with or without chronic renal failure, and so on.…”
mentioning
confidence: 94%